Obesity and academic performances in adolescents - Nina Herlina; Julistio TB Djais; Kusnandi Rusmil (Indonesian Pediatric Society Publishing House, 2013)
Background Adolescence is a phase of dynamic development in human life, marked by rapid physical growth, in addition to mental, emotional, and social development. Adolescent obesity has been related to metabolic disease, in addition to psychological disorders, which may lead to a negative impact on academic performances. Objective To assess academic performances in adolescents with obesity Methods A cross-sectional study was conducted in Junior High School No. 14 in Bandung from December 2010 to July 2011. Subjects were aged 12 to 14 years, and were divided into two groups: obese or good nutritional status. Statistical analysis using Fisher's exact test was performed to assess the association of obesity and academic performances. T-test was used to compare subjects' mean mathematics and English performances in the two groups. Results There were 24D students who met the inclusion criteria. Since there were 40 obese subjects in the first group, we randomized the remaining students to obtain 40 subjects with good nutritional status for the second group. Best academic performances in mathematics and English was obtained mostly by subjects in the good nutrition group (38/40 and 39/40, respectively). Statistical analysis revealed a significant association of lower performances in mathematics (mean difference -2.8; 95%CI -5 to -0.6; P=0.043) and English (mean difference -1.9; 95%CI -3.5 to -0.2; P=0.001) to obesity. We also found a significant association of better mathematics (P=0.001) and English performances (P=0.004) to the father's occupation. Additional English lessons were not associated with higher English performances in the obese group (mean difference 0.2; 95%CI -2.9 to 3 .2; P=0.885). Conclusion Obese adolescents tend to have poorer academic performances compared to those with good nutritional status.